Identification and Validation of Candidate Genes Involved in Fatty Acid Content in Oil Palm by Genome-Wide Association Analysis - Xia, Wei; Luo, Tingting; Dou, Yajing; Zhang, Wei; Mason, Annaliese S.; Huang, Dongyi; Huang, Xiaolong; Tang, Wenqi; Wang, Jihua; Zhang, Chunyu; Xiao, Yong (Frontiers in Plant Science, 2019)
Oil palm (Elaeis guineensis) is the highest yielding oil crop per unit area worldwide, but its oil is considered unhealthy for human consumption due to its high palmitic acid content (C16:0). In order to facilitate breeding for fatty acid content in oil palm, genome-wide association analysis was used to identify and validate SNP markers and underlying candidate genes associated with fatty acid content in a diversity panel of 200 oil palm individuals. A total of 1 261 501 SNP markers had been previously developed according to SLAF-seq (specific locus amplified fragment sequencing). Based on GWAS analysis, 62 SNP markers were significantly associated with fatty acid composition, and in the flanking regions of these SNPs, A total of 223 candidate genes were identified. we found one gene (acyl-ACP thioesterase B genes) that was involved in fatty acid biosynthesis. The gene was associated with high palmic acid contents in the mesocarp. Overexpression the genes caused a significant increase in palmitic acid content.